Base editing reveals an essential role for NANOG in human embryogenesis - Oliver J. Bower; Ana E. R. Orsi; Riley McMahon; Desislava Staneva; Josephine R. Blagrove; Kashish Singh; Claire S. Simon; Afshan McCarthy; Patricia Garcia; Valerie Shaikly; Mohamed Taranissi; Martin Wilding; et al. (Nature, 2026)
Abstract Understanding how the first cell lineages in human development are specified and maintained has fundamental importance and clinical implications for regenerative medicine, infertility and pregnancy loss. Although mouse models have provided valuable insights into transcription factors regulating early development, translating these findings to human embryos has been limited by ethical, technical and biological constraints. Functional studies of transcription factors in human embryos have been hindered by nuclease-based genome editing approaches that induce genotoxicity 1–3 . Here, to overcome this, we applied ABE8e adenine base editing 4,5 to precisely target an exon splice donor site, resulting in a splicing defect and functional knockout of the developmental regulator NANOG in human embryos. This approach did not trigger genotoxicity and showed limited off-target editing. Loss of NANOG disrupts pluripotent epiblast specification and instead cells differentiate towards a primitive endoderm (yolk sac) or trophectoderm (placental) transcriptional programme. Retention of primitive endoderm differentiation in NANOG -edited human embryos reveals a functional compensation that is distinct from mouse, underscoring the importance of directly investigating human development. Our findings demonstrate an essential role for NANOG in human pluripotency and epiblast specification and highlight the utility of base editing for functional interrogation of human development.